Deep-water ports for Germany - Heino Greve (Intereconomics, 1972)
The world-wide trend in bulk shipping towards larger-sized vessels has in recent years evoked a discussion in the Federal Republic of Germany about the advisability of providing technical facilities for handling giant ships on the German coast. Such facilities do not yet exist. The issue retains great topical interest because more and more mass carriers drawing too much water to enter German ports with a full load are coming into use or are under construction.
Keywords: 330; Germany